Sytuacja językowa w Unii Europejskiej - Bańczerowski, Janusz (Slavia Centralis, 2020)
The linguistic situation in the European Union Issues of language and culture in the EU exhibit a complex pattern, and their proper management cannot be conceived of without taking into consideration the results of interlinguistic and intercultural research. EU citizens must be prepared to confront cultural and civilizational diversity and also to understand that diversity rather than receiving it as a threat to their national identity. Are educated EU citizens, for example, ready to come to grips with linguistic, cultural and civilizational diversity? Are they able to adequately treat and accept such diversity? What are they prepared to do in order to maintain and cultivate their own language, culture, and identity, as well as to hand them down to the next generation? These are the challenges that a nation and a sovereign state necessarily have to face. New EU member states, torn out of its former isolation, has suddenly found itself exposed to globalization processes.